The development of a node for a hardware reconfigurable parallel processor - Van Schaik, Carl Frans (Department of Electrical Engineering, 2016)
This dissertation concerns the design and implementation of a node for a hardware reconfigurable parallel processor. The hardware that was developed allows for the further development of a parallel processor with configurable hardware acceleration. Each node in the system has a standard microprocessor and reconfigurable logic device and has high speed communications channels for inter-node communication. The design of the node provided high-speed serial communications channels allowing the implementation of various network topographies. The node also provided a PCI master interface to provide an external interface and communicate with local nodes on the bus. A high speed RlSC processor provided communication and system control functions and the reconfigurable logic device provided communication interfaces and data processing functions. The node was designed and implemented as a PCI card that interfaced a standard PCI bus. VHDL designs for logic devices that provided system support were developed, VHDL designs for the reconfigurable logic FPGA and software including drivers and system software were written for the node. The 64-bit version Linux operating system was then ported to the processor providing a UNIX environment for the system. The node functioned as specified and parallel and hardware accelerated processing was demonstrated. The hardware acceleration was shown to provide substantial performance benefits for the system.